Implementasi Model Pembelajaran Mind Mapping dalam Meningkatkan Prestasi Belajar Siswa Kelas XI Mata Pelajaran Ekonomi Materi Ketenagakerjaan di SMA Tri Dharma Ende - Beda, Elis; Rawe, Aschari Senjahari (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This research aims to determine: (1) The implementation of the Mind Mapping learning model in learning Economics with Employment material for Class XI Students at Tri Dharma Ende High School. (2) Achievement in learning Economics with Employment Material for Class after applying the Mind Mapping model. The type of research used is classroom action research (PTK) which consists of two cycles. Each cycle has one meeting each. The subjects of this research were 15 class XI students at SMA Tri Dharma Ende. The data collection technique used is; (1) Observation, (2) Test and; (3) Documentation. The data analysis technique used uses the Kemmis & McTaggart model, in (Arikunto, 2010) The results of this research show that (1) the Mind Mapping Model can be applied well in learning Labor Economics material. This can be seen from the first cycle, the implementation level was 65.71% or included in the quite good category and increased in the second cycle by 80% or included in the good category. (2) Student learning achievement after applying the Mind Mapping model increased. This can be seen in cycle I where 11 people completed it or 73.33% and 4 people or 26.67% did not complete it. Increased in cycle II from 15 students to 100% completion level. Thus, the proposed action hypothesis "By applying the Mind Mapping learning model in Economics Learning and Employment Materials for Class XI Students at Tri Dharma Ende High School was declared accepted.